Дано

$$- x^{4} + 2 x^{2} y = 3$$

3 2 2
2*y – x *y = 4

$$- x^{2} y^{2} + 2 y^{3} = 4$$
Ответ
$$x_{1} = – sqrt{3}$$
=
$$- sqrt{3}$$
=

-1.73205080756888

$$y_{1} = 2$$
=
$$2$$
=

2

$$x_{2} = sqrt{3}$$
=
$$sqrt{3}$$
=

1.73205080756888

$$y_{2} = 2$$
=
$$2$$
=

2

$$x_{3} = – sqrt{- frac{1}{3} – frac{2 i}{3} sqrt{2}}$$
=
$$- frac{1}{3} sqrt{-3 – 6 sqrt{2} i}$$
=

-0.577350269189626 + 0.816496580927726*i

$$y_{3} = – frac{2}{3} + frac{2 i}{3} sqrt{2}$$
=
$$- frac{2}{3} + frac{2 i}{3} sqrt{2}$$
=

-0.666666666666667 + 0.942809041582063*i

$$x_{4} = sqrt{- frac{1}{3} – frac{2 i}{3} sqrt{2}}$$
=
$$frac{1}{3} sqrt{-3 – 6 sqrt{2} i}$$
=

0.577350269189626 – 0.816496580927726*i

$$y_{4} = – frac{2}{3} + frac{2 i}{3} sqrt{2}$$
=
$$- frac{2}{3} + frac{2 i}{3} sqrt{2}$$
=

-0.666666666666667 + 0.942809041582063*i

$$x_{5} = – sqrt{- frac{1}{3} + frac{2 i}{3} sqrt{2}}$$
=
$$- frac{1}{3} sqrt{-3 + 6 sqrt{2} i}$$
=

-0.577350269189626 – 0.816496580927726*i

$$y_{5} = – frac{2}{3} – frac{2 i}{3} sqrt{2}$$
=
$$- frac{2}{3} – frac{2 i}{3} sqrt{2}$$
=

-0.666666666666667 – 0.942809041582063*i

$$x_{6} = sqrt{- frac{1}{3} + frac{2 i}{3} sqrt{2}}$$
=
$$frac{1}{3} sqrt{-3 + 6 sqrt{2} i}$$
=

0.577350269189626 + 0.816496580927726*i

$$y_{6} = – frac{2}{3} – frac{2 i}{3} sqrt{2}$$
=
$$- frac{2}{3} – frac{2 i}{3} sqrt{2}$$
=

-0.666666666666667 – 0.942809041582063*i

Читайте также  1/2-3*m=5*(m-3*n)/2-3 19+9*n=3*(m+6*n)+4
   
4.77
Irangaj
Курсовые, рефераты, контрольные, тесты, задачи по праву, а также по остальным предметам.